Transcription factor p63 bookmarks and regulates dynamic enhancers during epidermal differentiation. (1st June 2015) - Kouwenhoven, Evelyn N; Oti, Martin; Niehues, Hanna; van Heeringen, Simon J; Schalkwijk, Joost; Stunnenberg, Hendrik G; van Bokhoven, Hans; Zhou, Huiqing
Abstract The transcription factor p63 plays a pivotal role in keratinocyte proliferation and differentiation in the epidermis. However, how p63 regulates epidermal genes during differentiation is not yet clear. Using epigenome profiling of differentiating human primary epidermal keratinocytes, we characterized a catalog of dynamically regulated genes and p63‐bound regulatory elements that are relevant for epithelial development and related diseases. p63‐bound regulatory elements occur as single or clustered enhancers, and remarkably, only a subset is active as defined by the co‐presence of the active enhancer mark histone modification H3K27ac in epidermal keratinocytes. We show that the dynamics of gene expression correlates with the activity of p63‐bound enhancers rather than with p63 binding itself. The activity of p63‐bound enhancers is likely determined by other transcription factors that cooperate with p63. Our data show that inactive p63‐bound enhancers in epidermal keratinocytes may be active during the development of other epithelial‐related structures such as limbs and suggest that p63 bookmarks genomic loci during the commitment of the epithelial lineage and regulates genes through temporal‐ and spatial‐specific active enhancers.